FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KESIAPSIAGAAN PEKERJA OBJEK WISATA BERMAIN SEMARANG - Alvira Choirinnissa; Bina Kurniawan; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Preparedness is an effort to minimize potential disasters to avoid fatalities and property losses. Preparedness can be caused by 3 factors, predisposing factors such as knowledge and attitudes, reinforcing factors such as perception supervision and SOP as well as enabling factors such as perception of emergency infrastructure. Amusement park is one of the places that need to get attention related to safety, especially the workers who is in charge of the rides and the visitors who use the rides. The purpose of this study is to analyzed the relation between knowledge, attitude, and perception of supervision, SOP, also emergency infrastructure with the preparedness of workers at Amusement Park in Semarang. The research method used is quantitative with cross sectional study. The subjects of this study are 17 workers at Amusement Park in Semarang. Based on statistical test of the relation with chi-square test shows that there is a correlation between perception of supervision (p value = 0.043) and emergency infrastructure (p value = 0.049) with the preparedness of workers at Amusement Park in Semarang. The researcher advises the management to provide knowledge of hazards that exist in the workplace, equipment conditions at the workplace and any potential accidents that can occur, assert in terms of workers supervision related to safe work, inspection of work equipment and workplace monitoring, as well as maximizing the availability of existing facilities and infrastructure. The researcher also advises the workers to ensures to always work safely according to the established procedures.